Measuring customer satisfaction and loyalty : survey design, use, and statistical analysis methods - Hayes, Bob E., 1963- (ASQ Quality Press, 2008)
"The third edition of this best-seller updates its detailed information about how to construct, evaluate, and use questionnaires, and adds an entirely new chapter on customer loyalty." "Readers will gain a sound grasp of the scientific methodology used to construct and use questionnaires utilizing the author's systematic approach. They will be able to pinpoint and focus on the most relevant topics, and study both the qualitative and quantitative aspects of questionnaire design and evaluation. These and many more important scientific principles are presented in simple, understandable terms."--Jacket.